Effect of cultivar and storage on laboratory quality traits of rice straw - Sharada, P.; Venkateswarlu, G.; Reddy, C.R.K.; Prasad, Kodukula V.S.V.; Ravi, D.; Jyothi, B.; Subba Rao, I.V.; Ramana Reddy, Y.; Blümmel, Michael (2016)
Rice straw from sixteen cultivars were analyzed for crude protein (CP), neutral (NDF) and acid (ADF) detergent fiber, acid detergent lignin (ADL), Silica, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) at the time of harvest and after three months of storage under shed. Surprisingly storage significantly (P < 0.0007) increased straw quality traits. Correlations between quality traits at harvest and after storage varied (CP: r = 0.86, P < 0.0007; NDF.· r =0.75, P = 0.008, ADF. r = 0.50, P = 0.05, ADL r = 033, P = 0.27, Silica. r = -0.02, P = 0.95, IVOMD. r = 058, P = 0.02; MEr= 0.58, P = 0.02) suggesting that changes in fodder quality ranking among cultivar could occur because of storage.